Magnetic and transport properties of the mixed 3d–5d–4f double perovskite Sm2CoIrO6. (25th June 2021) - Pradhan, Suman Kalyan; Dalal, Biswajit; Saha, Rafikul Ali; Datta, Raktim; Majumdar, Subham; De, Subodh Kumar
Abstract: Iridium-based double perovskites having mixed 3 d –5 d –4 f magnetic sub-lattices are expected to exhibit exotic magnetic phenomenon. In this paper, we report a study of structural, magnetic and transport properties of the mixed 3 d –5 d –4 f double perovskite Sm2 CoIrO6 (SMCO), which crystallizes in monoclinic structure with space group P 21 / n and the crystal symmetry remains same throughout the measured temperature down to 15 K. High resolution synchrotron x-ray diffraction reveals an isostructural phase transition around 104 K. Magnetization measurements on polycrystalline samples indicate that SMCO orders ferrimagnetically at T FiM = 104 K; while, a second transition is observed below 10 K due to the rare-earth (Sm 3+ ) ordering. The ferrimagnetic transition is well-understood by Néel's two-sublattice model, which is primarily ascribed to antiferromagnetic coupling between Co 2+ and Ir 4+ sub-lattices. Electronic transport measurement shows the insulting behaviour of SMCO, which follows Mott variable-range hopping conduction mechanism. However, dielectric measurements as a function of temperature rules out the presence of magneto dielectric coupling in this compound.